2018
DOI: 10.12968/ijtr.2018.25.12.628
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rearfoot alignment on static and dynamic postural stability

Abstract: Background/Aims: It has been postulated that foot alignment affects postural stability. However, previous studies reported contradicting results regarding the association between foot alignment and postural stability. Methods: A total of 216 healthy participants aged 15 to 24 years were recruited. Their rearfoot alignment was measured in non-weight bearing and weight-bearing positions. Their static balance was assessed using Balance Error Scoring System and dynamic balance by Star Excursion Balance Test. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…A study conducted by Fu GQ et al has shown no significant relationship of rear foot alignment with static and dynamic postural balance. 24 Another study Mun K-R et al has shown medial longitudinal arch height to be correlated with postural stability in anteroposterior direction, 25 however the relationship was non-significant (p>0.05), similar to the findings of the current study. Moreover, the sample size of Mun K-R's study was small, consisting of only 13 healthy young adults with a mean age of 28.08 years.…”
Section: Discussionsupporting
confidence: 87%
“…A study conducted by Fu GQ et al has shown no significant relationship of rear foot alignment with static and dynamic postural balance. 24 Another study Mun K-R et al has shown medial longitudinal arch height to be correlated with postural stability in anteroposterior direction, 25 however the relationship was non-significant (p>0.05), similar to the findings of the current study. Moreover, the sample size of Mun K-R's study was small, consisting of only 13 healthy young adults with a mean age of 28.08 years.…”
Section: Discussionsupporting
confidence: 87%
“…Mortality from these chronic diseases is highly associated with obesity [10]. Besides, obesity also increases loading at the weight-bearing joint, leading to functional locomotor disability, the main cause of physical inactivity that contributes eventually to increased morbidity and mortality [11][12][13]. In other words, obesity indirectly shortens life expectancy while directly impacting the individual's quality of life and psychological well-being as it could lead to depression or low self-esteem [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%